1995
DOI: 10.1254/jjp.69.43
|View full text |Cite
|
Sign up to set email alerts
|

ATP Receptor-Mediated Increase of Ca Ionophore-Stimulated Arachidonic Acid Release from PC12 Pheochromocytoma Cells

Abstract: ABSTRACT-PhospholipaseA2 has recently been proposed as the effector enzyme involved in the receptor-mediated release of arachidonic acid (AA). Released AA and its metabolites have been demonstrated to play an important role in the regulation of cell functions.[3H]AA release from prelabeled PC12 cells was stimulated by a Ca ionophore such as ionomycin or A23187. Although ATP and its effective analogs, adenosine 5'-O-(3-thiotrisphosphate) (ATPrS), 2-methylthio ATP and 3'-O-(4-benzoyl)benzoyl ATP, did not stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Previous studies have suggested that PC12 cells also contain P2Y (Sela et al 1991;Nikodijevic et al 1994;Murayama et al 1995) and P2U (Raha et al 1993;Majid et al 1993;Nikodijevic et al 1994;Barry and Cheek 1994) purinoceptors and it is possible that activation of these G-protein coupled receptors could have stimulated 45Ca 2+ influx through mobilisation of intracellular calcium and refilling of intracellular stores, particularly through capacitative mechanisms involving calcium-influx across the cell membrane. The potential involvement of such a mechanism in the 45Caa+ influx measurements made in the present study is unlikely, however, for a number of reasons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested that PC12 cells also contain P2Y (Sela et al 1991;Nikodijevic et al 1994;Murayama et al 1995) and P2U (Raha et al 1993;Majid et al 1993;Nikodijevic et al 1994;Barry and Cheek 1994) purinoceptors and it is possible that activation of these G-protein coupled receptors could have stimulated 45Ca 2+ influx through mobilisation of intracellular calcium and refilling of intracellular stores, particularly through capacitative mechanisms involving calcium-influx across the cell membrane. The potential involvement of such a mechanism in the 45Caa+ influx measurements made in the present study is unlikely, however, for a number of reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally for such studies stable cell lines expressing one or other of the various recombinant receptor types would be of choice. However, in their absence PC12 cells were utilised as an alternative since there is extensive evidence that they contain a number of P2 purinoceptor subtypes, and in particular an ATP-gated channel receptor, obtained using a wide range of techniques such as electrophysiology (Inoue et al 1989;Nakazawa et al 1990) fura-2 calcium measurements (Fasolato et al 1990;Nakazawa and Inoue 1992;Raha et al 1993;Kim and Rabin 1994;Barry and Cheek 1994;Gollasch and Hailer 1995), neurotransmitter release (Inoue et al 1989;Sela et al 1991;Majid et al 1992), arachadonic acid release (Murayama et al 1995), inositol phosphate accumulation (Murrin and Boarder 1992;Majid et al 1993;Raha et al 1993;Barry and Cheek 1994) and 45Ca2+ influx (Seta et al 1991;Kim and Rabin 1994). Indeed the P2X2 purinoceptor gene was cloned from this cell line by Brake et al (1994) and our own studies have identified mRNA for the P2Xa purinoceptor in the cells used in this study (C.B.…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of ACh-activated current by ATP has also been observed [709]. ATP, acting through P2Y receptors, leads to the release of arachidonic acid from PC12 cells [710]. Diadenosine tetraphosphate, probably acting via a P2Y receptor, increased [Ca 2+ ] i in PC12 cells [711].…”
Section: Phaeochromocytomamentioning
confidence: 92%
“…The method of detecting release of incorporated [ 3 H]‐arachidonic acid as an index of living whole cell membrane AA metabolism is well established. Thus, HPLC and TLC analyses have revealed that high amounts (≈ 90–99%) of released radioactivity in the presence of BSA is attributable to free AA (Kanterman et al , 1991; Piomelli et al , 1991; Muruyama et al , 1995). Baseline control levels of d.p.m.…”
Section: Methodsmentioning
confidence: 99%